The Rule of Law in an Era of Change Responses to Transnational Challenges and Threats (Springer Series on International Justice and Human Rights,, 2018)
This forward-thinking volume examines the rule of law from a global perspective, in the context of a growing array of transnational challenges and threats As the United Nations (UN) notes, the rule of law constitutes the basis "on which fair and just societies are built." The contributions to this volume provide insights to several emerging debates about what the rule of law means in the modern era of warfare and of massive and systematic human rights violations that call for robust and transparent accountability mechanisms and processes. The authors of this work examine several controversial topics, including: -The growing use of drones, and the morality of long distance use -The UN Security Council's evolving counterterrorism policies and practices -Victims' Rights and the effort to provide meaning and justice to victims and survivors of terrorism - The relationship between the International Criminal Court (ICC) and Truth and Reconciliation Commissions (TRCs) -The effectiveness of the international criminal justice process overall, with an eye to procedural fairness and justice. This timely work will be of interest to researchers in criminal justice, particularly with a focus on counter-terrorism and international justice, as well as international law, human rights, and international studies.